Do men slow down faster than women? - Wolfgang Maennig; Michael Stobernack (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2010)
This paper is the first test of differences between age-related reductions in the performance of men and women. The assumption that men age faster is obvious, because men's life expectancy is generally lower. In addition to other studies on age-related reduction in human performance, this paper examines the data taken from competitions on rowing machines, which have been standardized worldwide and which are hardly affected by weather or temperature. A third innovation is that this study looks for any potential ageing processes specific to gender and physique. Fourth, fractional polynomials have been added to the testing methodology. Contrary to intuition, we find evidence that women are affected by faster age-related reductions in performance.
Keywords: J16; J24; 330; labor productivity; ageing economics; economics of gender